2007
DOI: 10.1002/macp.200700135
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthetic Method for the Preparation of Star‐Shaped Polyisobutylene with Hyperbranched Polystyrene Core

Abstract: Friedel–Crafts self‐grafting of polystyrene (PSt) under quasiliving carbocationic polymerization was utilized to develop a new rapid one‐pot method for the preparation of star‐shaped polyisobutylene (PIB). First, the polymerization of isobutylene led to PIB with predetermined molecular weight ($\overline M _{\rm n}$ = 2 000) and narrow molecular weight distribution ($\overline M _{\rm w} /\overline M _{\rm n}$ = 1.03). Then addition of relatively small amount of styrene after isobutylene consumption yielded PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…The first side reaction decreases the active chain end concentration and thus the branching efficiency. The alkylation of the monomer is negligible, because the reaction rate of chain propagation is much higher than that of the Friedel‐Crafts alkylation 34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first side reaction decreases the active chain end concentration and thus the branching efficiency. The alkylation of the monomer is negligible, because the reaction rate of chain propagation is much higher than that of the Friedel‐Crafts alkylation 34…”
Section: Resultsmentioning
confidence: 99%
“…Due to these special properties, several attempts have been reported on the synthesis of highly branched polyisobutylenes so far 12–16, 20–33. Previously, it was found that intra‐ and intermolecular Friedel‐Crafts alkylation of the benzene rings of styrene (St) units in polystyrene (PSt) segments might occur by carbocationic chain ends 13, 16–23, 34, 35. This undesired side reaction was observed not only during the cationic polymerization of pure St,35 but in the case of the preparation of thermoplastic elastomer block copolymers composed of PIB and PSt13–19 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Friedel–Crafts alkylation could be useful for polymer reactions in cationic polymerizations because an aromatic ring reacts with an electrophile or an electron‐deficient species. For example, the use of the electrophilic reactions of aromatic groups has been examined as a novel synthetic tool for producing star‐shaped polymers, hyperbranched polymers or end‐functional polymers via the cationic polymerization of isobutylene or vinyl ethers . More reactive aromatic rings such as a naphthyl group could allow more facile synthesis of well‐defined polymers in cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an efficient reaction of living propagating cations with naphthalene rings, the propagating cations should have high reactivity, which allows the use of less reactive monomers for the synthesis. Highly reactive polyisobutylene or polystyrene carbocations were employed in the aforementioned synthesis using the Friedel–Crafts reaction . Another candidate for such less reactive monomers generating highly reactive species is p ‐acetoxystyrene (AcOSt).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the aspect of preparation of “star‐like” polymers, hyperbranched/dendritic chains are usually acted as a multisites functional core to produce grafting chains via “graft‐onto” or “graft‐from” strategy. However, the as‐prepared “star‐like” amphiphilic or double‐hydrophobic/hydrophilic polymers are generally made of a very small core and much longer grafting chains, because the hyperbranched/dendritic cores are mainly prepared from small‐molecular polymerizable monomer, instead of long polymer chains (macromonomers) . One can image that hyperbranched topology, instead of star topology, will finally govern the physical properties of graft copolymers in solution if the branched core size is much larger than the grafting chain size.…”
Section: Introductionmentioning
confidence: 99%